SOSIALISASI PERLINDUNGAN KONSUMEN TERHADAP PENGEMBALIAN UANG BELANJA PADA RETAIL-RETAIL MODERN DI KOTA TARAKAN - WIWIN DWI RATNA FEBRIYANTI WIWIN FEBRIYANTI (Universitas Negeri Gorontalo, 2024)
One of the tridharmas of higher education is carrying out community service, for this reason, we will discuss consumer protection regarding refunds for shopping at modern retailers in Tarakan City. This PPM implemented with a socialization model expected to be able to provide understanding to the community through MSMEs that are members of the North Kalimantan MSME Communication Forum (Fokutara) so that they better understand consumer rights in taking change from shopping and also so that business actors are aware of their obligations so that they are not arbitrary in rounding up change or returning it with candy/chocolate or for donations. As regulated in statutory regulations, business actors are required to prepare small changes to give back shopping money to consumers. If the perpetrator does not heed this, there will be a threat of imprisonment for one year and/or a maximum fine of IDR 200,0000,000 (two hundred million rupiah) as stated in Article 33 Paragraph 1 of the Currency Law. The money used in transactions must be in accordance with the money currently in circulation, the minimum rupiah denomination is Rp. 50,- (fifty rupiah)